Recuperação da estrutura de um Latossolo vermelho degradado utilizando lodo de esgoto - Bonini, Carolina Dos Santos Batista [UNESP]; Alves, Marlene Cristina [UNESP]; Montanari, Rafael [UNESP] (My University, 2015)
The aim of this study was to investigate the influence of sewage in the recovery of the structure of a degraded Red Latosol (Oxisol) being cultivated for 4 years with eucalyptus (Eucalyptus citriodora) and (Brachiaria decumbens) in Selvíria, MS, Brazil. We used a randomized block design with 6 treatments and 4 replications. The treatments were: control (without the use of sewage sludge and mineral fertilizers); mineral fertilizer, 30 t ha-1 of sewage sludge; 60 t ha-1 of sewage sludge, todos with soil cultivated with eucalyptus and pasture, and two witnesses: savannah vegetation and exposed soil. In 2007, we evaluated physical soil properties: the distribution of pore size, soil bulk density, distribution of soil aggregate stability and water; and chemical soil properties: phosphorus, potassium, calcium, magnesium, organic matter; potential acidity( pH), sum of bases, cation exchange capacity and base saturation, in depths: 0.00 to 0.05, 0.05-0.10, 0.10 -0.20 and 0.20-0.40 m; resistance to moisture penetration and gravity, in depths: 0.00 to 0.15, 0.15 to 0.30 and from 0.30 to 0.45 m. It is concluded that the sewage sludge yielded positive changes in soil structure and recovery of soil chemical properties.
Recovery of the structure of a degraded Red Latosol (Oxisol) using sewage sludge
Keywords: Brachiaria; Eucalyptus; Soil degradation; Soil organic matter; Soil structure